Identification TRIM46 as a Potential Biomarker and Therapeutic Target for Clear Cell Renal Cell Carcinoma Through Comprehensive Bioinformatics Analyses - Xiang-bin Ren (Frontiers Media S.A., 2021)
Background: Tripartite motif containing 46 was initially identified as the oncogene in several human tumors. However, the clinical value and potential functions of tripartite motif containing 46 (TRIM46) in clear cell renal cell carcinoma (ccRCC) remained largely unclear.Methods: The expressing patterns, clinical involvement, and prognostic values of TRIM46 were analyzed using the data obtained from TCGA and GEO databases. A nomogram was constructed to examine the outcome of patients with ccRCC. We estimated the association between TRIM46 with tumor immunity in ccRCC.Results: Tripartite motif containing 46 was highly expressed in ccRCC, and its upregulation revealed an unfavorable prognosis. A nomogram based on TRIM46 expressions and other independent prognostic factors could robustly predict the overall survival of tumor patients. TRIM46 has a strong positive correlation with NUMBL, CACNB1, THBS3, ROBO3, MAP3K12, ANKRD13D, PIF1, PRELID3A, ANKRD13B, and PCNX2. Mechanically, TRIM46 displayed regulatory functions in ccRCC progression via several tumor-associated pathways. Besides, we observed that TRIM46 was distinctly related to tumor immunity in ccRCC.Conclusions: Our findings provide a novel tumor promotive role regarding TRIM46 function in the malignant progression of ccRCC.